2015
DOI: 10.1002/poi3.89
|View full text |Cite
|
Sign up to set email alerts
|

Event Prediction With Learning Algorithms—A Study of Events Surrounding the Egyptian Revolution of 2011 on the Basis of Micro Blog Data

Abstract: We aim to predict activities of political nature influencing or reflecting societal‐scale behavior and beliefs by applying learning algorithms to Twitter data. This study focuses on capturing domestic events in Egypt from November 2009 to November 2013. To this extent we study un­derlying communication patterns by evaluating content and metadata of 1.3 million tweets through computationally supported classification, with­out targeting specific keywords or users from the Twitter stream. Support Vector Machine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…It has been applied in similar detection scenarios, including detection of online pornography (Tang et al, ) and hate speech (Burnap & Williams, ). We follow the standard process of LDA with Gibbs sampling (Blei, ; Boecking, Hall, & Schneider, ; McCallum, ): For each topic k …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been applied in similar detection scenarios, including detection of online pornography (Tang et al, ) and hate speech (Burnap & Williams, ). We follow the standard process of LDA with Gibbs sampling (Blei, ; Boecking, Hall, & Schneider, ; McCallum, ): For each topic k …”
Section: Methodsmentioning
confidence: 99%
“…Despite the global outlook of jihadists, the lingua franca of groups like ISIS is Arabic, which is poorly covered in the literature. This is important to note for any language‐based automated detection task, as it has been shown that prediction accuracy is best when the locally dominant language is also employed in conjunction with English (Boecking et al, ). Thus, a serious limitation to our approach is the lack of availability of validated Arabic NLP packages.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…Others use a cascade of text filters to directly extract tweets [1] or Tumblr posts [5] that identify planned unrest events. Another group retrospectively examines the Egyptian revolution of 2011, using Twitter user metadata, including graph features of user networks, to predict major events [6].…”
Section: Related Workmentioning
confidence: 99%
“…In spite of the prevalence and availability of Application Programming Interfaces (APIs), as well as commercial data mining packages, and an almost endless supply of papers and studies that focus on specific platforms [1,2,5,6,11,15,17], cross platform analyses are lacking in the social media analysis and broader computation social science corpus. This is an oversight, in an age where nearly half of social media users have multiple social media profiles [9].…”
Section: Introductionmentioning
confidence: 99%